A Self‐Assembled Biocompatible Nanoplatform for Multimodal MR/Fluorescence Imaging Assisted Photothermal Therapy and Prognosis Analysis. Issue 35 (7th August 2018) - Wang, Lirong; Lin, Hongyu; Chi, Xiaoqin; Sun, Chengjie; Huang, Jiaqi; Tang, Xiaoxue; Chen, Hongming; Luo, Xiangjie; Yin, Zhenyu; Gao, Jinhao
Abstract: The need for better imaging assisted cancer therapy calls for new biocompatible agents with excellent imaging and therapeutic capabilities. This study successfully fabricates albumin‐cooperated human serum albumin (HSA)‐GGD‐ICG nanoparticles (NPs), which are comprised of a magnetic resonance (MR) contrast agent, glycyrrhetinic‐acid‐modified gadolinium (III)‐1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetate (GGD), and a fluorescence (FL) dye, indocyanine green (ICG), for multimodal MR/FL imaging assisted cancer therapy. These HSA‐GGD‐ICG NPs with excellent biocompatibility are stable under physiological conditions, and exhibit enhanced T 1 contrast capability and improved fluorescence imaging capacity. In vitro experiments reveal an apparent effect of the NPs in killing tumor cells under low laser irradiation, due to the enhanced photothermal conversion efficiency (≈85.1%). Importantly, multimodal MR/FL imaging clearly shows the in vivo behaviors and the efficiency of tumor accumulation of HSA‐GGD‐ICG NPs, as confirmed by a pharmacokinetic study. With the guidance of multimodal imaging, photothermal therapy is subsequently conducted, which demonstrates again high photothermal conversion capability for eliminating tumors without relapse. Notably, real‐time monitoring of tumor ablation for prognosis and therapy evaluation is also achieved by MR imaging. This strategy of constructing nanoplatforms through albumin‐mediated methods is both convenient and efficient, which would enlighten the design of multimodal imaging assisted cancer therapy for potential clinical translation. Abstract : A new type of biocompatible albumin‐cooperated nanoparticles (NPs) are fabricated for multimodal imaging assisted cancer therapy. These NPs exhibit enhanced T 1 contrast capability and improved fluorescence imaging capacity. With the guidance of multimodal imaging, photothermal therapy is demonstrated for eliminating tumors without relapse. Moreover, real‐time monitoring of tumor ablation for prognosis analysis is achieved by magnetic resonance imaging.